A percepção dos professores sobre o processo de implementação dos currículos de referência no instituto federal de São Paulo/campus Suzano. - Lima, Layla Crist (2023)
Our research has as a reference secondary-level professional education and the curricular guidelines proposed by the Federal Institute of São Paulo with the implementation of reference curricula, amidst changes that occurred in legislation following the preparation of the BNCC and the reform of secondary education in São Paulo. 2017. It is possible to verify in the documents that constitute the IF guidelines, research as a scientific and pedagogical principle, recognizing it as one of the supports for social, human and economic development. The process of implementing IF's reference curricula has been under construction since 2019, and follows the institution's own guidelines, due to its academic autonomy. Therefore, the research object of this work focuses on curriculum policy, its foundations and implementation. Its main objective is to understand the perception of teachers and coordinators of the technical course in industrial automation at the IFSP Suzano campus regarding the reference curricula that are in the process of being implemented, in the context of the BNCC and the secondary education reform. The importance of understanding the perception of teachers and coordinators regarding the process was based on the fact that they are most responsible for the execution and implementation of reference curricula, whether through PPC's or in day-to-day practice in the classroom, considering the curriculum as an instrument of transformation in a society and that it exercises power over it. Initially, the documents that underlie the organization of the IFSP reference curricula were analyzed. Subsequently, three focus groups were held with teachers and coordinators of the industrial automation course integrated into high school: with two coordinators from the technical and common centers; with a group of four teachers from the technical core and; with four teachers from the common core, who were able to explain how the implementation process has been designed within the IFSP Suzano campus. One of the proposals of the reference curriculum was standardization so that students could benefit if they needed to transfer, but the timetable and essential knowledge of the courses defined within the limits of the reference curriculum is still something decided within each campus, valuing the administrative autonomy of each of them. The perception of teachers and coordinators is that implementation is taking place quickly, even though the process has been planned for a few years. Ongoing changes, such as the number of classes and the project integrating disciplines, for example, are factors that provoke resistance. Regarding the differences and similarities of the reference curricula with the BNCC and the secondary education reform, the most mentioned aspect was the 800-hour cut in the timetable of the common core of the Suzano campus. The volume of content in the curricula was also mentioned in the discussions as worrying, often the scene of disputes for space in the subjects, although teachers understand that they present decisive issues regarding the inseparability between teaching and research. Teachers and coordinators state that the process is recent, which makes evaluations and measuring results difficult. Finally, they mention that within three to five years it will be possible to make the necessary alignments so that the reference curriculum is fully implemented.